The new colonial politics in Indonesia: Representations in the documentary film Colonial Debris - Wahyudi, Dicky; Sujoko, Anang; Suatan, Joycelyn Abigail; Ginting, Carmenita Alexandra Gracianti; Putri, Nakeisha Joenanda (Universitas Padjadjaran, 2026)
Background: The documentary film Colonial Debris attempts to represent new colonial politics in Indonesia, providing a narrative of resource exploitation and agrarian conflict by corporations and state apparatus against indigenous peoples in Indonesia. Purpose: This study aims to reveal how the documentary film Colonial Debris represents new colonial politics in Indonesia through a system of visual signs. Method: This study uses qualitative content analysis with a semiotic approach, with data collection techniques in the form of film archive documentation, which obtained a corpus of 40 sign-objects from the film Colonial Debris. The data was analyzed using Pierce's semiotic method with a sign, object, and interpretant framework. Result: This study shows that the film Colonial Debris represents new colonial politics through visual narratives about colonial legacy in the Indonesia’s agrarian system; State-Corporate repression and criminalization of community resistance; Socio-ecological inequality; People's resistance and solidarity. The interrelationship of the film's visual sign system reveals the power imbalance and social inequality maintained by the state apparatus and corporations as the superior, and indigenous communities as the inferior. Conclusion: Colonial Debris depicts new colonial politics as a continuation of old colonialism, through signs of eviction, state apparatus, biased rules, and citizens' struggles refer to the object of state-corporate colonialism, forming an interpretant that positions Indigenous communities as the colonized. Implications: This study contributes to media and documentary film studies, particularly in postcolonial approach, by showing how documentary films can reveal postcolonial power dynamics and inequalities in society.